PENERAPAN FUNGSI SOSIAL ATAS TANAH DALAM PENETAPAN TANAH TERLANTAR OLEH BADAN PERTANAHAN NASIONAL (STUDI TERHADAP: KEPUTUSAN KEPALA BADAN PERTANAHAN NASIONAL REPUBLIK INDONESIA NO: 14/PTT-HGB/BPN RI/2014) - Agripina Agripina; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2019)
Land is a gift fr0m G0d that must be used t0 fulfill human needs. H0wever there are lands that have been aband0ned by the land right holder for years. Aband0nment of land has been c0mm0nly f0und in many rural areas in Ind0nesia. Aband0ned land is regulated in G0vernment Regulati0n Number 11 Year 2010 0n Disciplining and Emp0werment 0f Aband0ned Land. The land right h0lder is basically prohibited from abandoning the land. However, in case that the right h0lder left the land unused, n0t utilized in acc0rdance with the circumstances 0r the purp0se of granting the rights, it leads t0 legal c0nsequences such as the ab0liti0n of the land rights c0ncerned and the terminati0n 0f legal relati0ns and affirmed as land directly controlled by the state. Acc0rding to Article 6 Act No. 5 Of 1960 C0ncerning Basic Regulati0ns 0n Agrarian Principles, all rights 0n land have a s0cial function. The State can all0cate the aband0ned land f0r public interest c0nsidering land has n0t 0nly ec0nomic values, but als0 s0cial values.